Australia - Hirsch, Rebecca E. (New York : Children's Press, 2013)
Simple text presents a short introduction to Australia.
Includes index.
2.2
K-3
Keywords: Australia -- Juvenile literature; Australia -- Geography -- Juvenile literature; Australia; Australia -- Geography; Australia; Australia -- Geography; Readers (Elementary)